Economic Drivers of Overseas Job Applications: The Mediating Role of Career Opportunities and Moderating Effect of Family Support - Febriyanti, Amanda Dwi; Aulia, Dea Islamey; Hermawan, Hendrik (Talent: Journal of Economics and Business, 2025)
In the context of increasing global labor mobility driven by economic pressures and limited domestic career prospects, understanding the determinants of overseas job interest becomes highly relevant. This study aims to examine the influence of economic factors on the interest in applying for jobs abroad, considering the mediating role of career opportunities and the moderating role of family support. A quantitative approach was employed using a survey method with questionnaires distributed to 149 respondents, and the data were analyzed using SmartPLS 3 software. The results indicate that economic factors have a positive and significant effect on the interest in working abroad, both directly and indirectly through the mediation of career opportunities. However, family support was not found to significantly moderate the relationship between economic factors and job application interest. These findings suggest that while economic conditions and career prospects play a crucial role in encouraging interest in working abroad, family support does not significantly influence this relationship. In conclusion, improving economic conditions and perceived career opportunities are the primary drivers of interest in working overseas, whereas family support is not a determining factor in this context.